PERANCANGAN SISTEM INFORMASI PENJUALAN PADA TOKO SUPER EMA GROSIR BERBASIS WEB - Apriliansyah, Ahmad M; Mahmudin, Mahmudin (Universitas Islam Syekh Yusuf, 2023)
Along with current technological developments, the use of computers is becoming a good alternative in information processing, and better when compared to processing information or data that still uses a manual system. Transaction and marketing in Super Ema Grosir which is still very simple and manual so it is less efficient, and the turnover generated by the Super Ema store Wholesale is a bit due to less extensive marketing media. Currently also a Super shop Ema Grosir still records sales data manually, from these problems then a marketing and sales website will be designed in this store. As is the website for marketing and sales that will be made is expected to help sales at the Super Ema Grosir store, and are expected to increase the turnover that will be obtained. This website was created using the PHP and MYSQL programming languages database. The results of this study are that the order process is running faster and efficiently without having to come to the store. By implementing an online sales system then the admin will find it easier to manage stock and sales data.